A New Approach for SAR Image Denoising - Murali Mohan Babu. Y; Subramanyam M. V.; Giri Prasad. M. N (Institute of Advanced Engineering and Science, 2015)
In synthetic aperture radar (SAR) imaging, the transmitted pulses from space born antenna interacts with ground objects and returned energy or back scattered energy will be collected to get backscattered image. In this process, a speckle noise will be added because of the coherent imaging system and makes the study of SAR images very difficult. For better SAR image processing, the speckle has to be removed in the initial stages of processing and maintain all texture features efficiently. The BM3D method is generally considered as state of art method in denoising of SAR images. In this paper, it is proposed a technique to despeckle the speckle noise to the maximum extent while maintaining the edge characteristics.